What's the Matter with "China"? A Critique of Teleological History. Issue 2 (26th February 2018) - Clark, Hugh R.
Abstract : This article argues that the study of China's history has long been caught in a teleological trap that presumes that history could have had only one evolutionary track. The author explains how he came to recognize the problems inherent in the teleological trap and to reconceptualize his approach. The article contrasts the history of the North China Plain, culturally rooted in dry-land grain agriculture and from time immemorial deeply intertwined with that of the adjacent grasslands, with that of the south, a culturally and linguistically diverse land of river valleys and riziculture. It concludes that the holistic empire we know today was not an inevitable outcome of these contrasting trajectories and that alternative paths are plausible, and asserts that scholars must recognize that until history is accomplished it does not follow a teleological trajectory.